Islamic genealogy in Bali: the legities of Wali Pitu in a cross-cultural perspective / Raselly Elfa Putri, Yulia Rohmawati and Rafida Mumtaz - Putri, Raselly Elfa; Rohmawati, Yulia; Mumtaz, Rafida (Academy of Contemporary Islamic Studies (ACIS), 2024)
Recent research found that approximately 10.07% the Muslim population in Bali ranks second as the lowest percentage in Indonesia. This low number contradicts with our ancestors massively deployed Islam, as evidenced by the legacy of Wali Pitu who undertook Islamic da'wah in Bali. To decipher, Wali Pitu is a term that refers to the seven clerics for spreading Islam in Bali. Qualitative descriptive through literature is applied to unravel the legacy of Wali Pitu in the perspective of cross-cultural studies. Furthermore, the existence of Wali Pitu in the development of Islam in Bali is something unique to recognize since it experienced different phase compared to Wali Songo in Java. In contrast to the Wali Songo whose existence has been well-renowned for a long time based on archaeological and historical searches, the public's belief in Wali Pitu is based on the sacred seven graves of Islam spreaders in Bali. In addition, the construction of Wali Pitu's sacredness only exists in the contemporary context introduced by Habib Toyyib Zaen Arifin Assegaf, a scholar from Sidoarjo, through a long process. Wali Pitu still has a pivotal role in spreading Islam in Bali. This is reflected in the structure of Balinese society with the existence of Muslim communities, the establishment of mosques, Islamic educational institutions (Islamic boarding schools), as well as other cultural acculturation products. It can be concluded that the legacy of Islam in Bali spread by Wali Pitu has had a significant impact on the development of Balinese culture today.